A case of multiple myeloma presenting with uric acid kidney stones. Issue 2 (June 2019) - Salameh, Hassan; Sirac, Christophe; Bender, Sébastien; Hamadah, Abdurrahman; Cornell, Lynn D; Chiu, April; Fornoni, Alessia; Leung, Nelson
Kidney disease is common in patients with multiple myeloma. Patients often present with acute kidney failure most commonly the result of light chain cast nephropathy. Presentation can also be in the form of nephrotic syndrome associated with immunoglobulin light chain amyloidosis or monoclonal immunoglobulin deposition disease and tubulopathy as in acquired light chain Fanconi syndrome. We present a case of a 56-year-old male with multiple myeloma who presented with chronic kidney disease and uric acid stones. Chemical analysis of the nephrolithiasis showed it to be entirely composed of uric acid. Fractional excretion of uric acid was elevated at 35.9%. Kidney biopsy was consistent with light chain proximal tubulopathy. Bone marrow biopsy showed 30% kappa light chain–restricted plasma cells. Genetic sequencing identified the light chain to be from the Vk1-33 subgroup. The patient was treated with bortezomib, cyclophosphamide, and dexamethasone, with improvement of his kidney function. This case illustrates a rare presentation of multiple myeloma.